2023
DOI: 10.26434/chemrxiv-2023-p621k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imaging voids and defects inside Li-ion cathode LiNi0.6Mn0.2Co0.2O2 single crystals

Abstract: Li-ion battery cathode active materials obtained from different sources or preparation methods often exhibit broadly divergent performance and stability, despite no obvious differences in morphology, purity, and crystallinity. We show how state-of-theart, commercial, nominally single crystalline LiNi0.6Mn0.2Co0.2O2 (NMC-622) particles possess extensive internal nanostructure even in the pristine state. Scanning X-ray diffraction microscopy reveals the presence of interlayer strain gradients and crystal bending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The application of recently developed highresolution X-ray and electron diffraction techniques to single-crystal cathode particles also revealed a more intricate and complex microscale misorientation framework than previously suggested. As was shown for certain nickel manganese cobalt (NMC) and LCO cathode that the microstructure of primary particles with seemingly perfect lattice structure can exhibit various degrees of tilt heterogeneities such as grain boundaries [7,23,11] which cause the development of cracks in the particles. Furthermore, it was demonstrated that the absence of domain boundaries in NMC cathode materials enhances the oxygen redox processes during prolonged cycles [10].…”
Section: Introductionmentioning
confidence: 99%
“…The application of recently developed highresolution X-ray and electron diffraction techniques to single-crystal cathode particles also revealed a more intricate and complex microscale misorientation framework than previously suggested. As was shown for certain nickel manganese cobalt (NMC) and LCO cathode that the microstructure of primary particles with seemingly perfect lattice structure can exhibit various degrees of tilt heterogeneities such as grain boundaries [7,23,11] which cause the development of cracks in the particles. Furthermore, it was demonstrated that the absence of domain boundaries in NMC cathode materials enhances the oxygen redox processes during prolonged cycles [10].…”
Section: Introductionmentioning
confidence: 99%